PENGARUH INFORMATION SHARING, KNOWLEDGE SHARING DAN RELATION TERHADAP PERFORMANCE PERUSAHAAN - Nirmala Mandasari; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2016)
In the 21st century is a lot going on to high competition in all fields, especially in the field of global free trade. More than a decade ago, the leaders of ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, Brunei Darussalam, Vietnam, Laos, Myanmar, and Cambodia) have agreed to form a single market in Southeast Asia in late 2015. The high level of competition is not only experienced by big companies but also to the small and medium enterprises in Indonesia, such as small and medium industries in Sub furniture Tahunan Jepara regency. The purpose of this study was to determine the effect of information sharing, knowledge sharing, and relation to the performance of the company. This type of research is explanatory research. The sampling technique using non-probability sampling techniques. The total sample of 70 respondents, using a sampling technique that is saturated with a certain considerations. This study uses qualitative and quantitative analysis techniques. Quantitative analysis using validity, reliability test, correlation coefficient, simple regression analysis, coefficient of determination, significance test (t test) using SPSS 16.0. The results of this study indicate that the company's performance can be explained by information sharing with the result of 36.9% amounting to 6,301 t count> t table 1.9955. The company's performance can be explained by knowledge sharing by 30.9% with the results of the t calculate equal to 5.511> t table 1.9955. The company's performance can be explained by a 42.8% relation to hasilt calculate equal to 7.134> t table 1.9955. Suggestions in this research that employers should always share information (information sharing) between the human resources that exist in the organization, but it is also needed to share knowledge (knowledge sharing) which will provide convenience to every employee with their innovation. From the sharing of information and knowledge sharing are also needed in a firm relation, a relation (relation) who nurtured will produce menuntungkan mutual relationships between one another. With the sharing of information, knowledge sharing, and relations can improve company performance.